Correlative Evaluation Between Nickel Ion Concentrations Doped in Some River Side Water Bodies of NënShkodra Lowland and Root Growth of Allium cepa (L.) - Mesi (Dizdari), Anila; Kopliku, Ditika; Neziri, Anila; Golemi, Suzana (Asian Journal of Chemistry, 2012)
In this investigation, the Allium test was applied to detect the inhibition of root growth by six nickel concentrations, doped in four riverside water sampes from NënShkodra lowland. Significant growth inhibition started at 0.5-1 × 10-4 M Ni2+ concentrations in all samples compared to drinking water control. Nickel concentrations higher than 5 × 10-4 M did not demonstrate any cumulative inhibitory effect. Mean root length and toxic effective concentrations values indicated the same decreasing amount and toxicity range of Ni2+ loaded samples: Bahçellek > Zues > Oblikë e Madhe > Obot i Vjetër > control. Based on EC50 values, nickel concentration in drinking water should be decreased by a factor of: 3.9, 2.7, 1.5 and 1.45 to obtain the same root growth inhibition effect corresponding to: Bahçellek, Zues, Oblikë and Obot. This biotest could screen nickel quantal and toxic tendency of analyzed natural waters.